The Relationship Between Working Time, Age, And Workload With Work Fatigue In Processing Workers At Ptpn Iv Regional 1 Pks Rambutan - Suzani Adina; Delfrina Ayu Astuty (International Journal of Health, Economics, and Social Sciences (IJHESS), 2026)
Background: Fatigue is the second leading cause of death after heart disease. Workers in the processing section are very vulnerable to work-related fatigue which can have negative impacts on them. Purpose: To determine the relationship between work tenure, age, and workload on work fatigue among workers at PT Perkebunan Nusantara IV Regional 1 PKS Rambutan, Tebing Tinggi City. Method: This study uses a quantitative research design with a cross-sectional approach, involving a sample of 56 respondents. Result: Data collection was carried out using a questionnaire with Chi-Square test analysis. The Chi-Square test results indicate a significant relationship between work tenure and work fatigue with a p-value = 0.027, and a relationship between workload and work fatigue with a p-value = 0.038. This study found a relationship between work tenure and workload with work fatigue among the processing workers at PTPN IV Regional 1 PKS Rambutan and the absence of a relationship between age and work fatigue.